Tellers, Makers, and Holders of Stories: A Micro-Analytic Understanding of Students’ Identity Work in Drama-based Adult ESL Classrooms - Kim, Won (Canadian Journal of Applied Linguistics, 2021)
Despite a wide-spread pedagogical interest and scholarly conviction in the possibilities of educational drama for creating more contextually-situated, engaging, and multi-modal L2 learning experiences (Piazzoli, 2018; Stinson & Winston, 2011), there is scarce empirical evidence concerning what is actually taking place interactionally in L2 classrooms for adults. This article presents a bottom-up microanalysis of classroom interaction in an ESL class in Canada with over 16 adult learners designed to explore the potential and actual impact of educational drama on classroom discourse and students’ L2 learning experiences. Using a discourse analytic approach (Antaki & Widdicombe, 1998; Goffman, 1981), I analyze the dynamic identity work of the class participants. The article presents empirically-grounded research findings that illustrate instances of interaction in and through which drama-based ESL pedagogy contributes to the development of dialogic and democratic classroom discourse and fosters a transformative empowering interpersonal space (Cummins, 2011).